Electronic Patient Reported Outcome Measures and quality of life in cancer (E-PROMISE): systematic review of the evidence and meta-analysis - Abdulqadir J Nashwan; Russell Kabir; Muhammad Aaqib Shamim; Pradeep Dwivedi; Noor Husain; Zarrin Ansari; Zahid Zahiri; Mamta Singh; Shambo Samrat Samajdar; Dinesh Dhodi; Bijaya Kumar Padhi; Aiman Zehra Kazmi; et al. (BMJ Open Quality)
Objective The objective of this systematic review and meta-analysis (SRMA) was to evaluate the impact of electronic patient-reported outcomes (ePROs) on health-related quality of life (HRQoL) in patients with cancer.Design We performed SRMA of randomised controlled trials (RCTs) comparing ePRO interventions with usual care in patients with cancer. The primary outcome was HRQoL. We used a random effects model a priori due to the anticipated clinical heterogeneity. Subgroup analyses and meta-regressions were performed to explore sources of heterogeneity. After assessing the risk of bias using risk-of-bias tool (RoB V.2), we rated the evidence certainty using the Grading of Recommendations, Assessment, Development and Evaluations framework.Eligibility criteria We included studies meeting the following criteria: (1) RCTs; (2) patients diagnosed with any type of cancer, undergoing or having completed treatment; (3) comparing ePROs with usual care without ePRO interventions; (4) assessing the effect on HRQoL.Information sources We systematically searched PubMed, Embase, and the Cochrane Central Register of Controlled Trials up to April 2024.Results We screened 7706 records to include 36 RCTs with 9608 patients. ePRO interventions showed a standardised mean difference (SMD) of 0.35; 95% CI 0.18 to 0.51 compared with usual care. Patients receiving ongoing therapy had an SMD of 0.39 (95% CI 0.21 to 0.58), while those who had completed therapy had an SMD of 0.12 (95% CI 0.01 to 0.22), with a significant subgroup difference (p=0.01). No statistically significant differences were observed across the method of ePRO assessment, cancer site, metastasis status, therapy status, average age or duration of ePRO use. The results remained consistent with Bayesian and other sensitivity analyses.Conclusions ePRO interventions improve HRQoL more than usual care in patients with cancer, with greater effect in those currently undergoing therapy. This improvement is independent of cancer type, duration of ePRO use or patient age. Future research should address sources of heterogeneity, explore long-term impacts and develop strategies to increase patient engagement and adherence to ePRO systems.PROSPERO registration number CRD42024531708.